Status of Higher Legal Education and Student Requirements in Realizing a Justice Law - Saragih, Sepriandison; Simanjuntak, Hotmaida (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This writing aims to determine the capacity of law higher education and law students in creating law enforcers who have integrity, professionalism, and are able to realize legal justice. The method used is descriptive qualitative method through a phenomenological approach, we examine data using critical data coding, in-depth interpretation and drawing conclusions which are answers to this research question by adhering to the principles of high validity and reliability. Next, we describe the data in the findings section by adding criticism and discussion to understand whether this data is relevant to answering the problem. For the reporting stage, we choose qualitative data reporting depending on data or literature review, which we limit to information and data released between 2010 and 2021 to find the latest information and data. Law enforcement in Indonesia that does not synergize with one another will hinder realization of justice. Therefore the existence of law higher education and law students as the forerunner of law enforcement must be questioned. The results of this study are that law enforcement in Indonesia still shows ineffectiveness in its operations. So the authors suggest that higher education in law must be oriented towards efforts to provide stimulus to students so that they are able to have critical, analytical, innovative and progressive thinking so that the essence of law enforcement, namely justice, can be achieved.